Documentación del sistema de la gestión de la calidad bajo la NTC ISO 9001:2015 para la empresa Distribuidora Tropiquindio S.A.S. de Armenia, Quindío. (2016)
This draft grade reflects the work developed during the internship at the company TROPIQUINDIO S.A.S. What is the PROPOSES Process Documentation Standard NTC ISO 9001: 2015, fines Con implement, if desired. Development of this work was first made a diagnosis of the Front Company to the requirements of the Standard, Where It should be noted that one reason for any having implemented the standard without interest in doing so, the diagnosis gives total one of any Developed. Then it passed to define Strategic Platform, where the Mission, Vision, Quality Policy, Quality Objectives and Corporate values are established. Once the strategic planning defined, we proceeded to inquire what were the processes that interact in the Organization and Process Map is designed with its characterization: procedures and required to have a mayor of Knowledge Process approach of the organization. And finally Required Program Design internal audit for monitoring, measurement and control of the processes for applying: corrective actions, or Preventive Improvement